The Potential of Corn Waste (zea mays L.) as Ruminants Feed in Bolo District, Bima Regency - Mastur Mastur; Oscar Yanuarianto; Dedy Supriadin; Ridwan Saedi; Yusuf Akhyar Sutaryono; Sukarne Sukarne (Jurnal Biologi Tropis, 2022)
Corn straw as agricultural waste is a source of feed for ruminants which has a high fiber content and still contains good nutritional value and is sufficiently available. Unfortunately, this potency has not been fully utilized by the farmer as animal feed. This condition is found in almost all regions in NTB because we still see a lot of corn straw or corn waste in general, a lot of which is wasted even burned by the community. One of the efforts that need be made so that it can be used as a source of feed is by knowing the production of corn straw and its potential as feed for ruminants in Bolo District, Bima Regency. The research was carried out by survey method by using a questionnaire. The research results showed that the area of ​​maize plants in Bolo District was 4,041.88 hectares with a harvest area of ​​3,024.76 hectares. The production of corn waste consisting of stalks, leaves, husks, cobs and silk was 3,629.66 tons in dry matter. The population of ruminants (cattle, buffalo, goats and sheep) is 10,008 heads with the largest livestock population is the cattle. From the calculation between the amount of corn waste production and the ruminant livestock population in Bolo District, Bima Regency, it can be concluded that corn waste has a high potential as feed, which is 19 percent.